C4d Deposition and Cellular Infiltrates as Markers of Acute Rejection in Rat Models of Orthotopic Lung Transplantation - Murata, Kazunori (2008)
BACKGROUND: C4d is a useful marker of antibody-mediated rejection in cardiac and renal transplants, but clinical studies examining correlations between circulating alloantibodies, C4d deposition, and rejection in lung transplants have yielded conflicting results. METHODS: We studied circulating alloantibody levels and C4d deposition in two rat models of lung transplantation: Brown Norway (BN) to Wistar-Kyoto (WKY) and PVG.R8 to PVG.1U lung allografts. The availability of C6 deficient (C6−) and C6 sufficient (C6+) PVG 1U rats allowed evaluation of the effects of the terminal complement components on graft injury and C4d deposition. RESULTS: The lung allografts had histologic features resembling human posttransplant capillaritis, characterized by neutrophilic infiltration of alveoli, edema, and hemorrhage. Immunoperoxidase stains on cross sections of allografts showed intense, diffuse, C4d deposition in a continuous linear pattern on the vascular endothelium. C4d deposits were found in both BN to WKY and PVG R8 to 1U allografts, whereas no staining was detectable in WKY to WKY isografts or native lungs. Complement deposition was associated with vascular disruption in C6−, but not in C6+ recipients. The presence of circulating donor-specific alloantibodies was verified by flow cytometry. Cell-specific staining revealed perivascular accumulation of macrophages and T lymphocytes whereas neutrophils were sequestered in the intravascular and alveolar capillary compartments. CONCLUSIONS: The deposition of C4d on vascular endothelium as well as the coincident presence of alloantibodies is consistent with previous findings in antibody-mediated rejection of renal and cardiac transplants. Furthermore, the histological features of our allografts support the concept that posttransplant capillaritis is a form of humoral rejection.